Weaving Wisdom into Words: E-Modules for Short Story Writing Inspired by South Sumatra's Heritage - Anisa'u Fitriyatus Sholihah; Indrawati, Sri; Izzah, Izzah (REiLA : Journal of Research and Innovation in Language, 2024)
The integration of digital tools in education often overlooks the potential of cultural enrichment in teaching materials, especially in enhancing writing skills. This study pioneers the development of e-modules infused with South Sumatra's local wisdom, aiming to fill this gap by offering a unique blend of tradition and technology in short story text writing. Employing a Research and Development (R&D) approach, this study involved a needs analysis, prototype development, and iterative testing phases, including small group trials and field trials with 60 students from SMA Negeri 1 Lempuing Jaya and feedback from two Indonesian language teachers. Data were collected through questionnaires, interviews, document checklists, and pretest-posttest measures to evaluate the e-modules' practicality, validity, and effectiveness. The created e-module, integrating procedures for writing short story texts with South Sumatra's local wisdom, achieved a validation score of 81.93% (valid), a practicality score of 93.4% (very practical), and demonstrated a significant improvement in students' writing skills, with a pretest-posttest improvement showing a 2-tailed p-value of <0.0001. This e-module not only bridges the cultural gap in digital educational resources but also highlights the efficacy of local wisdom in enhancing educational outcomes. The significant improvements in student writing skills underscore the potential for such culturally integrated e-modules to serve as a model for future educational materials. These findings advocate for a broader adoption and development of culturally relevant educational tools, emphasizing their role in preserving cultural heritage and improving educational quality.